S-duality for the Large N = 4 Superconformal Algebra - Creutzig, Thomas; Gaiotto, Davide; Linshaw, Andrew R. (Communications in Mathematical Physics, 2020)
We prove some conjectures about vertex algebras which emerge in gauge theory constructions associated to the geometric Langlands program. In particular, we present the conjectural kernel vertex algebra for the ST2S duality transformation in SU(2) gauge theory. We find a surprising coincidence, which gives a powerful hint about the nature of the corresponding duality wall. Concretely, we determine the branching rules for the small N= 4 superconformal algebra at central charge - 9 as well as for the generic large N= 4 superconformal algebra at central charge - 6. Moreover we obtain the affine vertex superalgebra of osp(1 | 2) and the N= 1 superconformal algebra times a free fermion as quantum Hamiltonian reductions of the large N= 4 superconformal algebras at c= - 6.
CRIS-Team Scopus Importer:2024-06-24